Analisis Manajemen Risiko pada UMKM Kerupuk Adie Mandiri Menggunakan Metode HOR - Saragih Manihuruk, Hendrik Vicarlo; Riswana, Elsya; Valentine, Teresa Novinda Putri; Zahrany, Annisa Nur (SURYA TEKNIKA, 2025)
The cracker industry is a growing food sector in Indonesia. UMKM Kerupuk Adie Mandiri in North Balikpapan produces onion crackers made from garlic. This study aims to analyze the risks in its production process using the House of Risk (HOR) method. This method helps identify, classify, and prioritize risks based on impact and probability. Business process identification was carried out using the SCOR approach and 19 risk events and 28 risk causes were found. With HOR 1 and the help of the Pareto diagram, 3 dominant risk causes were selected. A total of 13 mitigation strategies were formulated, and through HOR 2, strategies that were easy and dif icult to implement were determined. These results are expected to help UMKM in risk management and increasing operational ef iciency, and can be a reference for similar industries.